2015
DOI: 10.1111/tid.12340
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of clofazimine as salvage therapy for atypical mycobacterial infection in solid organ transplant recipients

Abstract: Clofazimine appears safe and may be considered as a salvage therapeutic option in SOT recipients with MAC infection who are intolerant or unresponsive to standard therapy. The small sample size does not allow conclusions regarding efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…This antimicrobial was recently introduced for the treatment of multidrug-resistant or extensively drug-resistant tuberculosis (14)(15)(16)(17). Several reports have also reported the clinical efficacy of CFZ in the treatment of Mycobacterium avium complex lung disease (18)(19)(20)(21)(22); however, the results are inconsistent. Regarding M. abscessus infection, in vitro DST studies demonstrated a low MIC of CFZ and in vitro synergy between CFZ and other antibiotics, such as clarithromycin (CLR), AMK, or tigecycline (23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…This antimicrobial was recently introduced for the treatment of multidrug-resistant or extensively drug-resistant tuberculosis (14)(15)(16)(17). Several reports have also reported the clinical efficacy of CFZ in the treatment of Mycobacterium avium complex lung disease (18)(19)(20)(21)(22); however, the results are inconsistent. Regarding M. abscessus infection, in vitro DST studies demonstrated a low MIC of CFZ and in vitro synergy between CFZ and other antibiotics, such as clarithromycin (CLR), AMK, or tigecycline (23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 77%
“…Notably, a recent experimental study reported that CFZ prevented the regrowth of the M. abscessus type strain exposed to AMK and CLR (28). Although the experimental studies cited above suggest a potential role for CFZ in the treatment of NTM lung disease, several clinical studies evaluating the efficacy of CFZ for the treatment of M. avium complex lung disease reported inconsistent response rates (18)(19)(20)(21)(22), and clinical data on the outcomes of patients with M. abscessus lung disease treated with CFZ are extremely limited (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that soluble CFZ is toxic in vitro, with a 50% inhibitory concentration of approximately 5 M, whereas the insoluble crystalline form of CFZ that bioaccumulates in macrophages leads to very few signs of toxicity even at 100 M (23). Indeed, in spite of its massive accumulation in the liver, the hepatotoxicity of CFZ in mice and human patients has not been a significant concern (45)(46)(47). Like humans, mice treated with therapeutic CFZ doses (10 mg/kg/day) did not show signs of deteriorated health.…”
Section: Figmentioning
confidence: 99%
“…The use of clofazimine in combination therapy has been associated with sputum conversion and favorable treatment outcomes for MAC pulmonary disease. [66][67][68] Clofazimine also has a synergistic effect with amikacin, macrolides, and other antimicrobials for M abscessus complex, and it is often used for this difficultto-treat disease, but effectiveness data are limited. [69][70][71] Clofazimine is usually well tolerated.…”
Section: Clofaziminementioning
confidence: 99%